Effects of relative age on physical and physiological performance characteristics in youth soccer - Bliss, A.; Brickley, G. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: In youth sport, birth-date positioning of performers has significant implications for future success. This phenomenon is particularly evident in soccer and is identified as the "Relative Age Effect" (RAE). To date, limited work has been conducted into the RAE from a laboratory setting. METHODS: Subjects completed a modified cycling intermittent sprint protocol (mCISP) of 15, 6 s sprints against a resistance of 7.5%·body mass, interspersed with 120 s active recovery. Nineteen (male) athletes (mean±SD) age 14.2±0.7 y; height 164±7.9 cm and body mass 54±8.7 kg participated and were separated into six-month groups, Early-Born (EB) or Late-Born (LB) based on birth-month. Ethical approval was granted by the University Ethics Committee. RESULTS:Statistically significant differences (P<0.05) were found between EB and LB peak power outputs (PPO) and mean power outputs (MPO) (absolute and relative to body mass). EB subjects had significantly higher inter-sprint MPOs and PPOs for 15 and 13 sprints respectively. Borderline significance was observed for height and fat free mass (P=0.11). CONCLUSION: The present study suggests EB individuals are often more physically and physiologically mature than LB counterparts.